2015
DOI: 10.5194/bg-12-6181-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevated CO<sub>2</sub> on organic matter pools and fluxes in a summer Baltic Sea plankton community

Abstract: Abstract. Ocean acidification is expected to influence plankton community structure and biogeochemical element cycles. To date, the response of plankton communities to elevated CO 2 has been studied primarily during nutrient-stimulated blooms. In this CO 2 manipulation study, we used largevolume (∼ 55 m 3 ) pelagic in situ mesocosms to enclose a natural summer, post-spring-bloom plankton assemblage in the Baltic Sea to investigate the response of organic matter pools to ocean acidification. The carbonate syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
157
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(175 citation statements)
references
References 88 publications
16
157
1
1
Order By: Relevance
“…Nine mesocosms (M1-M9) were moored in the open waters of the Storfjärden (5951.5 • N, 2315.5 • E) at a water depth of ∼ 30 m. Only six of them were included throughout the whole study period since leakages in the remaining three rendered them unusable. Equipment and deployment procedures are described in detail by Paul et al (2015b). Briefly, polyurethane enclosure bags of 2 m in diameter and 18.5 m in length were mounted in floating frames and lowered in such a way that ∼ 17 m of each bag was immersed in the water column and ∼ 1.5 m remained above the water surface.…”
Section: Experimental Design and Co 2 Manipulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine mesocosms (M1-M9) were moored in the open waters of the Storfjärden (5951.5 • N, 2315.5 • E) at a water depth of ∼ 30 m. Only six of them were included throughout the whole study period since leakages in the remaining three rendered them unusable. Equipment and deployment procedures are described in detail by Paul et al (2015b). Briefly, polyurethane enclosure bags of 2 m in diameter and 18.5 m in length were mounted in floating frames and lowered in such a way that ∼ 17 m of each bag was immersed in the water column and ∼ 1.5 m remained above the water surface.…”
Section: Experimental Design and Co 2 Manipulationmentioning
confidence: 99%
“…The intended CO 2 and pH gradients were reached after the last treatment on day 4. Details are described in Paul et al (2015b). For the two untreated (control) mesocosms, only filtered fjord water was added to adjust the water volume to that of the treated mesocosms.…”
Section: Experimental Design and Co 2 Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…While these studies helped in developing a principal understanding of how OA affects the physiology of single species, we are still largely lacking the understanding of how OA effects may manifest on the community level (Riebesell and Gattuso, 2015). Existing "whole community" studies show that both direct effects of OA on single species and indirect effects through changes in plankton community structure (Hall-Spencer et al, 2008;Fabricius et al, 2011;Schulz et al, 2013;Paul et al, 2015;Bach et al, 2016;Gazeau et al, 2016) can significantly influence biogeochemical cycles in the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Recent mesocosm experiments showed that OA effects can be particularly pronounced during extended periods of low inorganic nutrient concentrations (Paul et al, 2015;Sala et al, 2015;Bach et al, 2016;Thomson et al, 2016). We therefore conducted an in situ mesocosm experiment in the eastern subtropical Atlantic Ocean off the coast of Gran Canaria (Canary Islands)-a region characterized by low concentrations of inorganic nutrients in particular during fall when the study took place (Arístegui et al, 2001).…”
Section: Introductionmentioning
confidence: 99%